2019
DOI: 10.1001/jamasurg.2018.1162
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sexual Functioning in Women and Men in the 5 Years After Bariatric Surgery

Abstract: IMPORTANCE Short-term improvements in sexual functioning are reported after bariatric surgery, but to our knowledge, little is known about the durability of these improvements. OBJECTIVE To determine the percentage of adults with impairment in sexual functioning who experience durable improvements in sexual functioning after bariatric surgery and to identify factors associated with improvements. DESIGN, SETTING, AND PARTICIPANTS The Longitudinal Assessment of Bariatric Surgery-2 is an observational cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 50 publications
5
24
0
3
Order By: Relevance
“…Sexual function was significantly improved, in accordance with several previous studies on sexual functioning after bariatric surgery. 17 , 18 , 30 Improvements in sexual life after bariatric surgery have previously been linked to a decrease in BMI and also linked to decreased body image dissatisfaction. 31 In a study on women with polycystic ovary syndrome and normal, overweight, and obese BMI, there was a negative correlation between HADS-A and HADS-D and the FSFI total score, suggesting a link between body dissatisfaction, distorted self-perceived body image, sexual dysfunction, and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual function was significantly improved, in accordance with several previous studies on sexual functioning after bariatric surgery. 17 , 18 , 30 Improvements in sexual life after bariatric surgery have previously been linked to a decrease in BMI and also linked to decreased body image dissatisfaction. 31 In a study on women with polycystic ovary syndrome and normal, overweight, and obese BMI, there was a negative correlation between HADS-A and HADS-D and the FSFI total score, suggesting a link between body dissatisfaction, distorted self-perceived body image, sexual dysfunction, and depression.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Female sexual dysfunction improves after bariatric surgery. 17 , 18 There is also some evidence that the incidence of pregnancies increases after bariatric surgery, but the mechanisms behind this effect remain unknown. 19 , 20 In a previous qualitative study, young childless women had high expectations on getting back to a normal life including better sexual health and improved fertility.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis conducted by Coulman et al (2017), it was shown that bariatric surgery had positive effects on physical health, psychological health, sexual life and body image by leading to weight loss in individuals. In another study, approximately half the men and women that were not satisfied with their sexual lives before bariatric surgery experienced an improvement in satisfaction during the 5-year follow-up (Steffen et al, 2019). Unlike our study, the authors evaluated the sexual function of both genders, but not their partners.…”
Section: Discussionmentioning
confidence: 80%
“…At this time, 73.6% (95% CI: 69.3%-78.0%) of the women who had physical limitations to sexual activity before bariatric surgery still reported an improvement. The improvement was independent of the type of surgical procedure [20].…”
Section: Female Sexuality and Sexual Functionmentioning
confidence: 77%